2003
DOI: 10.1007/s00203-003-0595-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and partial characterization of the gene encoding the putative elongation factor Ts of Streptococcus suis serotype�2

Abstract: Streptococcus suis infection has a substantial impact on the swine industry. In addition, S. suis serotype 2 is recognized as a zoonotic agent. In this paper, we report the cloning and complete sequence of the gene coding for the putative elongation factor Ts ( tsf-like) of S. suis. The putative tsf gene seems to be transcribed from a promoter located within the cloned DNA fragment, as its expression is not dependent on insertional orientation within the plasmid. One copy of the tsf gene was detected in the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The other nine proteins of APEC exhibiting immunoreactivity were previously unidentified. Among these, GroEL, AtpD, MalE, Tsf and Pnp have been shown to be immunogenic in other species [36][37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…The other nine proteins of APEC exhibiting immunoreactivity were previously unidentified. Among these, GroEL, AtpD, MalE, Tsf and Pnp have been shown to be immunogenic in other species [36][37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…Ef‐Ts is a surface‐associated protein in other streptococci, such as Streptococcus oralis (Wilkins et al ., 2003) and S. pyogenes (Cole et al ., 2005). Martinez et al . (2003) reported that Ef‐Ts expressed by all reference strains of all S. suis serotypes are antigenically similar, as determined by Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%